Salmonella Effector SteA Suppresses Proinflammatory Responses of the Host by Interfering With IκB Degradation - Gulati, Aakanksha; Shukla, Rhythm; Mukhopadhaya, Arunika (Frontiers in Immunology, 2019)
Salmonella enterica serovar Typhimurium is known to cause its virulence by secreting various effector proteins directly into the host cytoplasm via two distinct type III secretion systems (T3SS-1 and T3SS-2). Generally, T3SS-1 delivered effectors help S. Typhimurium in the early phases of infection including invasion, immune modulation of the host cells, whereas, T3SS-2 effectors mainly help in the survival of S. Typhimurium within the host cells including maintenance of Salmonella-containing vacuole (SCV), replication of the bacteria and dissemination. Some of the effectors are secreted via both T3SS-1 and T3SS-2, suggesting their role in distinct phases of infection of host cells. SteA is such an effector which is secreted by both T3SS-1 and T3SS-2. It has been shown to control the membrane dynamics of the SCV within the host cells in the late-phases of infection. In this manuscript, towards characterizing the T3SS-1 function of SteA, we found that SteA supresses inflammatory responses of the host by interfering with the NF-κB pathway. Our initial observation showed that the mice infected with steA-deleted S. Typhimurium (ΔsteA) died earlier compared to the wild type bacteria due to heightened immune responses, which indicated that SteA might suppress immune responses. Further, our study revealed that SteA suppresses immune responses in macrophages by interfering with the degradation of IκB, the inhibitor of NF-κB. SteA suppresses the ubiquitination and hence degradation of IκB by acting on Cullin-1 of the SCF (Skp-1, Cullin-1, F-box)-E3 ligase complex. Our study revealed that SteA suppresses a key step necessary for E3 ligase activation, i.e., neddylation of Cullin-1 by interfering with dissociation of its inhibitor Cand-1.